A highly sensitive FET-type aptasensor using flower-like MoS2 nanospheres for real-time detection of arsenic(iii). Issue 22 (22nd May 2017) - An, Ji Hyun; Jang, Jyongsik
Abstract : MoS2 -based FET aptasensor exhibited a rapid response, high sensitivity, and outstanding selectivity. Abstract : Arsenic (As) contamination in drinking water is problematic due to its threat to human health. Highly stable, sensitive and selective sensors are needed for As(iii ), which is the most toxic of the various forms of arsenic. Herein, we describe the fabrication of field-effect transistor (FET)-type aptasensors for As(iii ) detection that is based on carboxylic polypyrrole (CPPy)-coated flower-like MoS2 nanospheres (CFMNSs). Arsenic-binding aptamer-conjugated CFMNSs were integrated into a liquid-ion gated FET system, leading to extraordinary performance with a rapid response (on a time scale of less than 1 s). Field-induced current changes occurred through the interaction between the aptamer and As(iii ), resulting in sensitive discrimination of As(iii ) at unprecedentedly low concentrations ( ca. 1 pM). Moreover, the CFMNS-based aptasensor selectively recognized As(iii ) among numerous other metal ions and accurately detected As(iii ) in a mixed solution. The FET aptasensor could also discriminate target analytes in a real sample derived from river water. This MoS2 -based aptasensor is a promising tool for the detection of As(iii ) and could be used in a wide range of practical applications.